Prevention of Diabetes Mellitus Focusing on Diet Patterns and Blood Sugar Check - Novitayanti, Eka; Rahmayanti, Yeni Nur; Proborini, Christiana Arin (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
The incidence of diabetes is projected to continue to increase to 643 million in 2030. If this continues, the number will jump to 783 million people in 2045, So it is important to improve health status by providing education on the prevention of diabetes mellitus with a focus on diet and blood sugar checks in adults. The aim of this community service is to detect diabetes mellitus early and prevent it in the community. Efforts are being made to improve health status by providing diabetes mellitus education with a focus on diet and blood sugar checks. The pre-test results showed that most of the 20 respondents (70.8%) had quite good knowledge, the post-test results showed that 45 respondents (100%) had good knowledge. The results of the GDS examination were obtained from 28 respondents, 7 respondents detected high GDS. It can be concluded that there is an increase in knowledge after being given counseling, so it is very important that this community service is implemented.